Formação continuada do professor de matemática : contribuições das Tecnologias da Informação e Comunicação para prática pedagógica - Santos, Josiane Cordeiro de Sousa (2018)
The present research seeks to investigate how the continuous training for the use of ICT can contribute to the pedagogical practice of mathematics teachers, based on theoretical assumptions of mathematics teaching, as well as the following specific objectives: Identify public policies for continuing education of teachers for the use of ICT that have passed through the municipality of Estância; To describe the ICTs used by teachers of mathematics in the classroom and to analyze the insertion of ICT in mathematics classes by teachers who participated in continuing education courses and their results in the teaching-learning process. In order to reach the proposed objectives, a qualitative research approach was chosen, with a methodological design of a case study using questionnaire and observation techniques applied to teachers who teach the Mathematics discipline in a municipal public school in Estância / SE. For this, a theoretical framework was built, supported by the studies of Borba (2014), Castells (2006), Fazenda (2011), Kenski (2006 and 2007), Lévy (1997), Nóvoa (1995), Triviños ), Rosa Neto (2001), Vasconcelos (2017) among other authors who base the questions about the use of ICT in Mathematics teaching. The realization of this study made it possible to know the context in which the research took place, the actions of the subjects involved and the space of research on ICT as an instrument in the pedagogical practice of the Mathematics teacher. When analyzing the insertion of ICT in Mathematics classes by teachers who participated in continuing education courses and their results in the teaching-learning process, it was possible to perceive that they are used in the practice of teachers, but there are still teachers who remain unrelated to it them as a pedagogical resource. Finding that, in a subtle way, some changes in the pedagogical practice of teachers regarding the use of ICT in their classes were identified.